Meta-Analysis of the Efficacy of Laparoscopic Pyeloplasty for Ureteropelvic Junction Obstruction via Retroperitoneal and Transperitoneal Approaches - Ji, Fengming; Chen, Li; Wu, Chengchuang; Li, Jinrong; Hang, Yu; Yan, Bing (Frontiers in Pediatrics, 2021)
Objective: This study aimed to evaluate the clinical efficacy of laparoscopic pyeloplasty (LP) for ureteropelvic junction obstruction (UPJO) via retroperitoneal and transperitoneal approaches. Method: A systematic literature search on key words was under taking using PubMed, Cochrane Library, Embase, China Nation Knowledge (CNKI), and Wanfang. The eligible literature was screened according to inclusion and exclusion criteria. Meta-analysis was performed by using RevMan 5.0 software. Results: According to the inclusion and exclusion criteria, 12 studies were identified with a total of 777 patients. 408 patients were treated with retroperitoneal laparoscopic pyeloplasty (RLP) and 368 patients were treated with transperitoneal laparoscopic pyeloplasty (TLP). The meta-analysis results showed that the two approaches were similar in term of presence of on postoperative hospital stay, postoperative complication, the rate of conversion and recurrence (P＞0.05). The operative time in TLP group was significantly shorter than RLP group (MD=16.60；95% CI，3.40～29.80；P=0.01). The duration of drainage was significantly shorter (MD=-1.06；95% CI，-1.92～-0.19；P=0.02) and the score of postoperative visual analogue score (VAS) was significantly lower in RLP group than TLP group (MD=-0.52；95% CI，-0.96～-0.08；P=0.02). Conclusion: Both approaches have good success rate and low postoperative complication rate. RLP provides a shorter duration of drainage and lower VAS score, but it takes more operative time than TLP.